Lighting, housing and health: contributions of the 2030 Agenda for sustainable cities and communities - Mendes, Élgen Soares; Toledo, Renata Ferraz de (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2022)
As an important factor in the promotion of environmental comfort, lighting in houses has been increasingly analyzed in studies about health and well-being. Understanding how human exposure to light (artificial or natural) can influence health and the possible beneficial or harmful aspects can contribute to developing strategies that optimize its use and effects, both on human health and on sustainability. Thus, the objectives of this research were to analyze if, and how, lighting in houses can influence human health and determine if the lighting, housing and health topics are connected to the 2030 Agenda Sustainable Development Goals (SDGs). This is a bibliographic review carried out through searches in the Scientific Electronic Library online and EBSCO Information Services databases, based on the following descriptors: lighting, health, housing, environmental comfort and sustainable development, some of their synonyms and in different combinations, researched in Portuguese and English. Other criteria were also used to select the publications to be analyzed, which, in turn, gave rise to two thematic groups: the first addressing environmental comfort in housing, analyzing its relationship with the residents’ health and listing important elements for the promotion of environmental comfort; and the second devoted to specifically analyzing the relationship between lighting and human health. When analyzed in an interdisciplinary and intersectoral way, we understand that the “lighting-housing-health” relationship can be connected to the SDGs and effectively contribute to the 2030 Agenda.